Association of High Calorie Food and Coffee Consumption Pattern, Sleep Duration and Stress Level with Nutritional Status in Final Year Students - Permata Aprilia Putri (Universitas Airlangga, 2022)
Background:The habit of consuming high-calorie foods and drinking coffee with high sugar level is a habit that many final year students have, which is related with the duration of sleep and the burden of high academic demands that they have, so they are at risk of experiencing nutritional problems that end up affecting their nutritional status such as increasing the risk obesity.Objectives: The purpose of this study was to analyze the association between the habit of drinking coffee and high-calorie foods consumption, sleep duration and stress levels with nutritional status in final year studentsMethods:This research was using a case-control research design. The sample size used in this study was 50 final year students at Faculty of Public Health Universitas Airlangga which were categorized into 2 group with 25 respondent in each group. Sample selected by simple random sampling method. The data obtained were analyzed using the independent t-test, and logistic regression test followed by the received dataResults: The results of this study showed there is relation between the habit of drinking espresso-based coffee (p = 0.000), the frequency of drinking coffee (p = 0.018), the volume of drinking coffee (p = 0.046), the habit of drinking coffee at night (p = 0.008), consumption of high-calorie foods (p=0.000), intake from high-calorie foods [energy (p=0.000), carbohydrates (p=0.000), protein (p=0.000), fat (p=0.002)], nutrient adequacy level from high-calorie foods [energy (p=0.000), carbohydrates (p=0.000), protein (p=0.000), fat (p=0.000)], sleep duration (p=0.048) with nutritional status. However, there was no relation was found between stress level with nutritional status (p=0.646).Conclusions:Obese respondents tend to have a habit of drinking coffee frequently with high sugar content, and often consuming high-calorie foods and having a short sleep duration compared to the non-obese group. But both groups of respondents have moderate levels of stress. Dietary regulation and sleep duration are recommended for respondents in an effort to reduce the risk of obesity